Design and performance analysis of small hole throttling aerostatic bearings - QIU Dezhong; LEI Weining; XUE Yaping (Jixie qiangdu)
Focusing on the performance of single-throttle-orifice aerostatic bearings, this study investigates the effects of design parameters on load capacity and stiffness, aiming to optimize the structural design and performance of aerostatic bearings. A parametric model of the single-throttle-orifice aerostatic bearing was developed using the finite element method. The influence of factors such as air cavity design, throttle orifice diameter, supply air pressure, air film thickness, throttle orifice depth, air cavity thickness, and air cavity diameter on bearing performance was analyzed. Simulation and experimental testing were combined to validate the influence of design parameters on bearing performance. The results indicate that throttle orifice diameter, air film thickness, supply air pressure, and air cavity diameter significantly affect the bearing's load capacity, while throttle orifice depth and air cavity thickness have a smaller impact. Parameters such as throttle orifice diameter, supply air pressure, air cavity diameter, and air cavity thickness positively correlate with load capacity, whereas air film thickness and throttle orifice depth negatively correlate. Additionally, aerostatic bearing with air cavity structures exhibit superior load capacity and stiffness compared to those without air cavities. The consistency between simulation results and experimental data confirms the reliability and accuracy of the proposed simulation model.